Mengupas Bentuk Dilema Dari Sisi Konsultan Pajak - Dewi, Anak Agung Istri Pradnyarani; Sudarma, Made; Baridwan, Zaki (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 1 (2019), 2019)
This study aims to explore how the natural shape of the dilemmas in tax consulting and how the experience of overcoming dilemmas, is felt especially when doing tax planning. The qualitative method has been used with the interpretive paradigm according to the approach of transcendental phenomenology of Husserl. The informant in this study is a tax consultant of IKPI Denpasar. The research results reveal that dilemma forms tax consultants such that the dilemma posed by tax consultants have concern for the client and tax consultants think of business continuity services. The dilemma forms generate tax consulting experience in overcoming the perceived dilemma that is by building awareness of the taxpayer and must be aware of the profession as a tax consultant who is bound by the code of conduct. The dilemma can be overcome by building awareness of taxpayers and having strong principles to comply with the code of ethics. Keywords : Ethical Dilemma, Tax Consultants, Tax Planning, Taxpayer Compliance, Phenomenology